Risk of death due to other causes is lower among octogenarians with non-small cell lung cancer after wedge resection than lobectomy/segmentectomy. (30th July 2021) - Mimae, Takahiro; Miyata, Yoshihiro; Yoshimura, Kenichi; Tsutani, Yasuhiro; Imai, Kentaro; Ito, Hiroyuki; Nakayama, Haruhiko; Ikeda, Norihiko; Okada, Morihito
Abstract: Objective: We aimed to determine the influences of surgical procedures on the postoperative death of octogenarians with clinical Stage IA non-small cell lung cancer excluding cT1mi. Methods: We compared overall survival and the cumulative incidence of death due to all and other causes among 1 130 279, and 191 consecutive patients aged ≤79 and ≥80 years after lobectomy, segmentectomy and wedge resection at three institutions. Death due to other causes was defined as death due to any cause except non-small cell lung cancer. Results: The median followup was 53 months. The 5-year overall survival rates for patients aged ≥ 80 and ≤ 79 years after lobectomy, segmentectomy and wedge resection were respectively, 78.0% (95% confidence interval, 63.8%–87.2%) versus 91.2% (95% confidence interval, 89.0%–92.9%), 68.1% (95% confidence interval, 45.2%–83.1%) versus 90.0% (95% confidence interval, 84.6%–93.5%), and 62.7% (95% confidence interval, 44.0–76.7%) versus 84.4% (95% confidence interval, 76.3%–89.9%) ( P < 0.01 for all). The cumulative incidence of death due to other causes after wedge resection was similar between patients aged ≥ 80 and ≤ 79 years ( P = 0.45), but significantly higher in those aged ≥ 80, than ≤ 79 years after lobectomy or segmentectomy ( P = 0.00015 and 0.00091, respectively). Conclusions: The influence of wedge resection on death due to other causes was lower than that of lobectomy or segmentectomy in patients with non-small cell lung cancer aged ≥ 80 years. Wedge resection might be a useful option for octogenarians even if they can tolerate lobectomy/segmentectomy to avoid postoperative death due to causes other than non-small cell lung cancer. Abstract : This study provides useful information with which to determine optimal surgical procedures for patients aged ≥ 80 years. Wedge resection is useful for octogenarians with non-small cell lung cancer, especially considering postoperative death due to other causes.